Ultrastructure of the spermatozoon of the digenean Tergestia acanthocephala (Stossich, 1887) (Gymnophalloidea: Fellodistomidae): An intestinal parasite of Belone belone gracilis (Pisces: Teleostei). Issue 3 (June 2015) - Kacem, H.; Ndiaye, P.I.; Neifar, L.; Torres, J.; Miquel, J.
Abstract The ultrastructural organization of the spermatozoon of the digenean Tergestia acanthocephala (Gymnophalloidea: Fellodistomidae) is described. Live digeneans were collected from Belone belone gracilis (Teleostei: Belonidae), caught off the Gulf of Gabès in Chebba (Tunisia). The mature spermatozoon of T. acanthocephala exhibits the general pattern described in numerous digeneans, characterized by the presence of two axonemes of the different length of the 9 + '1' pattern of the Trepaxonemata, a nucleus, two mitochondria, two bundles of parallel cortical microtubules, external ornamentation, spine-like bodies and granules of glycogen. Moreover, the morphology of the posterior spermatozoon extremity in T. acanthocephala corresponds to the fasciolidean type of Quilichini et al. (2010a).